Membangun Karakter Santri yang Kreatif, Toleran, dan Bertanggung Jawab (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
Pesantren has several functions, among others, as a character education institution. Among the many characters that must be instilled in students, creative characters, tolerance, and responsibility are the three main character pillars. Creative characters need to be instilled in students so that students are not out of date. With a creative character, students will always seek and find new things in their lives. Tolerance is important for students because they will face diversity both inside and outside the pesantren. Responsibility is very important, because responsibility is a basic character that must be instilled early on in students. From these problems, motivation emerged to study efforts to build creative character, tolerance, and responsibility in students. This study uses a descriptive method with a qualitative approach. The results of this study indicate that efforts to build the students who have creativity, tolerance, and responsibility in general can be done by creating an environment that is creative, tolerant, and responsible. In particular, it can be done using a normative approach, a model approach, a reward and punishment approach, a value planting approach, a substantive learning approach, and a reflective learning approach.